Recent Development of Extremophilic Bacteria and Their Application in Biorefinery - Zhu, Daochen; Adebisi, Wasiu Adewale; Ahmad, Fiaz; Sethupathy, Sivasamy; Danso, Blessing; Sun, Jianzhong (Frontiers in Bioengineering and Biotechnology, 2020)
The biorefining technology for biofuels and chemicals from lignocellulosic biomass has made great progress in the world. However, mobilization of laboratory research to industrial setup needs to meet a series of issues, including the selection of appropriate pretreatment technology, breakthrough in enzyme screening, pathway optimization, and production technology, etc. Extremophiles play an important role in biorefinery, by providing novel metabolic pathways and catalytically stable/robust enzymes that can able to carry out biocatalysts under harsh industrial conditions on their own. This review summarized the potential application of thermophilic, psychrophilic alkaliphilic, acidophilic, halophilic bacteria and extremozymes in the pretreatment, saccharification, fermentation process and lignin valorization process. Besides, the latest studies on the engineering bacteria of extremophiles using metabolic engineering and synthetic biology technologies for high-efficiency biofuel production are also introduced. Furthermore, this review explores the comprehensive application potential of extremophiles and extremozymes in biorefinery due to their specificity and efficiency, and points out the necessity of accelerating the commercialization of extremozymes.